PENGARUH PENDIDIKAN KESEHATAN TENTANG MENARCHE TERHADAP PENGETAHUAN SISWI KELAS IV, V DAN VI DI SDN 01 BEKIRING KECAMATAN PULUNG KABUPATEN PONOROGO - Eliya Rohmah; Endang Setyowati (Akbid Harapan Mulya Ponorogo, 2019)
Menarche is the first menstruation that usually occurs at the age of 12-13 years, Menarche is the most important event in young women as a sign that the fertile cycle has begun. Based on the results of a preliminary study in November 2016 of 10 female students at SDN 01 Bekiring, 10 respondents said that those who had never had menstruation had 8 students (80%) who did not know about menarche and had never been given education about menarche. The purpose of this study was to analyze the influence of health education about menarche on the knowledge of grade IV, V and VI students at SDN 01 Bekiring, Pulung District, Ponorogo Regency. The research method used is a pre-experimental design with a one group pretest posttest approach. The population consisted of 40 grade IV, V and VI students. The sample in this study were 31 female students who attended the study. Sampling uses purposive sampling technique. With instruments for health education variables in this study are leaflets, LCD and SAP. The results showed that before being given health education 54.8% of respondents had sufficient knowledge, and after being given health education 58.1% were well-informed. While the results of the paired T-Test statistical test show that a significant value of 0,000. Which means "there is an influence of health education about menarche on the knowledge of class IV, V and VI students at SDN 01 Bekiring, Kec. Pulung Kab. Ponorogo ". It is recommended for puskesmas officers to hold counseling about menarche to other schools.